Medard Boss, life and work: The search for an understanding of the human being (Phenomenology, Humanities and Sciences, 2025)
In Brazilian literature on Daseinsanalysis, Medard Boss is presented as the physician who received support from Heidegger to found an approach to human health and disease. His entry into this story occurs after the emergence of Daseinsanalysis with Ludwig Binswanger, a psychiatrist who would later be disowned by the philosopher, bequeathing to Boss an open path to develop a therapy consistent with Heidegger's philosophy. Commentators suggest that Boss may have remained under the shadow of the philosopher. In such comments, there is a lack of depth in the Daseinsanalyse developed by Medard Boss in his work. This article aims to contribute to the presentation of Medard Boss's life and work as a search for an understanding of the human being. To do so, the method used is a bibliographic research, using the literature that presents his life and work, in addition to using writings by Medard Boss himself, especially a memoir written when he was 70 years old, to explain the foundations and meaning of Daseinsanalysis. Its focus is Boss’ biography up to the start of the Zollikon Seminars. His work has been heavily influenced by the works of Binswanger, Jung, Heidegger, and Boss’ travel experiences to India and Indonesia.
Keywords: Daseinsanalysis; Medard Boss; Phenomenology; Biography; Psychotherapy